SEDIMENTOLOGI DAN STRATIGRAFI ENDAPAN SUNGAI CITARUM DI WILAYAH PERALIHAN MORFOLOGI PEGUNUNGAN DAN DATARAN TINGGI BANDUNG ANTARA DESA CIKAWAO DAN DESA NAGRAK (KEC. PACET) DAN DESA SUKAMAJU (KEC. MAJALAYA), KAB. BANDUNG - Moechtar, H. (Jurnal Geologi dan Sumberdaya Mineral, 2011)
Citarum River deposits, which located at near Cikawao and Nagrag villages (Sub-district of Pacet) and Sukamaju village (Sub-district of Majalaya), Bandung District, consist of cobbles to boulders, sands to pebbles, sands, and clays. The research was carried by analysed sedimentology and stratigraphy of five vertical profiles with 1:20 scales, and the thickness of sediments vary from 1.6 to 4,0 m. Base on correlation, the sediment bodies can be devided into three Interval of Deposition Periods (IPP A to C), and ten of Sub-Interval of Deposition Periods (Sub-IPP A.1 to C.3).The lateral changes of sediments represented by each Sub-IPP, interpreted as result of internal processes such as morphology, energy, and flow. Vertically, changes of sediments that form nine steps of cobble to boulder resulted from the change of flow systems following climate change . It is understood that, the period of energy and flows correlate with climatic changes.Keywords: River channel, morphology, energy and flows, climate